A qualitative exploration of the older prisoner health and social care assessment and plan (OHSCAP) in a “dangerous” prison system - Forsyth, Katrina (The journal of forensic psychiatry & psychology, 2023)
Older prisoners are the fasted growing sub group in prisons across developed countries. They have high levels of health and social care needs in relation to their younger counterpart and those of the same age living in the community. There are a lack of interventions to ensure their needs are met. The older prisoner health and social care assessment and plan (OHSCAP) provided a structured process for addressing need and it’s effectiveness was evaluated in a randomised controlled trial (RCT). This paper presents findings from the nested qualitative study relating to this RCT. The aim of this study was to explore the facilitators and barriers to delivering the OHSCAP. Semi-structured interviews were conducted with twelve staff members delivering the OHSCAP and 14 service users who had received the intervention. The framework method was used to analyse the data produced. Participants described a ‘broken’ prison system. They discussed a staffing crisis resulting in individuals’ human rights being violated, which led to dangerous conditions in the prison. These conditions further impeding the staffing crisis, as recruitment was difficult and staff sickness was high. This ‘broken’ prison cycle significantly contributed to a lack of adequate attention being paid to OHSCAP processes. The delivery of health and social care interventions in prison is challenging when basic systems relating to staffing and safety are not adequate. Future research needs to consider how these circumstances can be mitigated.